Terminological Metaphor and the Emergence of Polysemy - Daliyeva, Madina (The Lingua Spectrum, 2025)
The article examines how terminological metaphor expands sense inventories and thereby generates polysemy. Building on cognitive metaphor theory (Lakoff & Johnson, 1980), sociocognitive terminology, and the Generative Lexicon (Pustejovsky, 1995), it traces systematic sense formation in scientific and public domains: cloud → cloud computing, platform → political platform, virus → computer virus, window → graphical user interface. Disambiguation relies on selectional preferences, collocations, and register cues, while translation choices depend on skopos and enregisterment (Vermeer, 2004; Bowker & Pearson, 2002). Corpus monitoring and prototype-based terminography help document the core–periphery structure of meanings (Geeraerts, 2010). The conclusion frames terminological metaphor as a productive mechanism of lexical growth that yields regular, manageable polysemy; practical guidelines are offered for lexicography, newsroom and technical stylebooks, and multilingual translation policies.